High temperature causes breakdown of S haplotype-dependent stigmatic self-incompatibility in self-incompatible Arabidopsis thaliana. (22nd July 2019) - Yamamoto, Masaya; Nishimura, Kenji; Kitashiba, Hiroyasu; Sakamoto, Wataru; Nishio, Takeshi
Abstract : High temperature disrupts the targeting of SRK to the plasma membrane, resulting in breakdown of the stigmatic self-incompatibility response in self-incompatible Arabidopsis transformants. Abstract: Commercial seeds of Brassicaceae vegetable crops are mostly F1 hybrids, the production of which depends on self-incompatibility during pollination. Self-incompatibility is known to be weakened by exposure to elevated temperatures, which may compromise future breeding and seed production. In the Brassicaceae, self-incompatibility is controlled by two genes, SRK and SCR, which function as female and male determinants of recognition specificity, respectively. However, the molecular mechanisms underlying the breakdown of self-incompatibility under high temperature are poorly understood. In this study, we examined the self-incompatibility phenotypes of self-incompatible Arabidopsis thaliana SRK-SCR transformants under normal (23 °C) and elevated (29 °C) temperatures. Exposure to elevated temperature caused defects in the stigmatic, but not the pollen, self-incompatibility response. In addition, differences in the response to elevated temperature were observed among different S haplotypes. Subcellular localization revealed that high temperature disrupted the targeting of SRK to the plasma membrane. SRK localization in plants transformed with different S haplotypes corresponded to their self-incompatibility phenotypes, further indicating that defects in SRK localization were responsible for the breakdown in the self-incompatibility response at high temperature. Our results provide new insights into the causes of instability in self-incompatibility phenotypes.